Developing Students’ Worksheet for English Language Teaching to Cope with the 4C’s Skill Through Project Based Learning - Nurhafni Siregar; Firmansyah Firmansyah; Yulia Sari Harahap (Universitas Pendidikan Mandalika, 2023)
This research aims to implement and evaluate design concepts and develop a PjBL-based students worksheet adapted to teaching materials to improve the 4C’s skill of Senior High School students in English subjects. Development research was used in this research. The PjBL-based students' worksheet was developed by matching the criteria for the components of the students' worksheet model: model syntax, social systems, management reaction principles, support systems, instructional impacts, and accompaniments, as well as other necessary instruments. The instruments developed were students' worksheet model validation sheets and learning tools validated by experts and practitioners. The data were analyzed by using descriptive statistical analysis. The results of this research indicated that the Project-based Learning (PjBL)-based students' worksheet model met the level of validity, practicality, and effectiveness to improve the 4C's skills of Senior High School students which contained: (a) syntax, (b) social system built on the principle of collaboration, (c) the principle of management reaction in which teachers act as facilitators, motivators, moderators, and consultants, (d) support systems in the form of Learning Implementation Plans, Teacher Books, Student Books, and Participant Worksheets Educate, (e) instructional impact in the form of students' 4C's skills and accompaniment impact in the form of critical thinking, creative thinking, responsibility, openness, and understanding of concepts.